New paleomagnetic data from the Antarctic Peninsula and their tectonic implications (Dataset) ... - A. M. Grunow (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: New paleomagnetic data from the Antarctic Peninsula and their tectonic implications ...